Seismic Behaviour of Reinforced Concrete Frames with Concentric Steel Bracing: A Review of Research from 1990 to 2023 - Birendra Kumar Bohara; Prasenjit Saha (Momentum International Journal of Civil Engineering (MIJCE), 2026)
This article offers an extensive review of research conducted between 1990 and 2023 on reinforced concrete (RC) frames retrofitted with concentric steel bracing systems, emphasizing their seismic performance, design strategies, and retrofitting efficacy. Different bracing configurations, including X-type, V-type, diagonal, inverted V-type, and knee bracing are assessed regarding energy dissipation, ductility, overstrength factors (R), stiffness, and failure mechanisms, as demonstrated through experimental and numerical studies. Significant findings underscore the importance of buckling-restrained braces (BRBs), post-tensioned systems, and self-centering cable braces in enhancing lateral load capacity, minimizing displacements, and boosting seismic resilience. The review also investigates pushover analyses to evaluate failure modes (such as weak-beam/strong-column mechanisms) and the effects of retrofitting on existing buildings. Design methods, including elastic steel frames and optimization of shear capacity, are thoroughly compared. Notable gaps in current methodologies, such as the necessity for standardized quantification of the R-factor and performance-based design protocols, are highlighted. Drawing on over three decades of research, this paper concludes with recommendations for the future, stressing the importance of advanced materials, hybrid systems, and AI-driven modeling to enhance concentric braced RC frames in response to emerging seismic challenges.